Book review: Vesuvius, Campi Flegrei and Campanian volcanism, by Benedetto De Vivo, Harvey E. Belkin and Giuseppe Rolandi (Eds.), 2019. Elsevier Inc., Amsterdam. 520 pages. Paperback: price 175.00, ISBN 9780128164549 - Scarpati, Claudio (Geologos, 2020)
Book review: Vesuvius, Campi Flegrei and Campanian volcanism, by Benedetto De Vivo, Harvey E. Belkin and Giuseppe Rolandi (Eds.), 2019. Elsevier Inc., Amsterdam. 520 pages. Paperback: price 175.00, ISBN 9780128164549